Characterization of Microstructure and Magnetic Properties of CaCu3Mn4O12 by Sol Gel Route - A.R.M, Warikh; A., Nurulhuda; A.R., Jeefferie (Universiti Putra Malaysia, 2011)
The crystallization of single phase CaCu3Mn4O12 (CCMO) was successfully synthesized via sol gel method and was fairly well densified at relative low temperature under atmospheric condition. The microstructure characteristic, phase formation and magnetic properties of CaCu3Mn4O12 ceramics were investigated and characterized by XRD, FESEM and VSM testing. It was found that the pure phase with highly crystalline of CaCu3Mn4O12 were formed after sintered at 700°C under atmospheric condition as support by XRD analysis. FESEM result shows the significant influence of sintering parameter on the microstructure behavior of CaCu3Mn4O12. The smaller particle size with higher grain boundary and less of porosity were found for the sample sintered at 700°C to 800°C. The samples show the ‘superparamagnetism’ behavior where the M-H curves are linear with the field and have a smaller value of coercivity at room temperature. Sintering at 800°C produced the sample with lowest Hc value due to the phenomenon over grown of magnetocrystallites, grain size and grain boundaries.